Question and answer
Subtract (9x^2 + 3x – 4) – (3x^2 +8x – 1)
Subtract (9x^2 + 3x – 4) – (3x^2 +8x – 1) = 6x^2-5x-3
Question
Asked 4/16/2013 12:17:40 PM
Updated 4/5/2014 2:50:04 PM
0 Answers/Comments
This answer has been confirmed as correct and helpful.
Edited by andrewpallarca [4/5/2014 2:50:03 PM], Confirmed by andrewpallarca [4/5/2014 2:50:04 PM]
s
Get an answer
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
Multiply (3x – 1)(x + 5)
Weegy: (3x – 1)(x + 5) = 3x^2 +14x - 5 User: When you find the zeros of a polynomial function, what are you finding? Weegy: When you find the zeros of a polynomial function, you are finding the ROOTS. (More)
Question
Expert Answered
Asked 4/16/2013 12:22:51 PM
0 Answers/Comments
Solve for x. (x+3)^2
Weegy: Solution: x/2 = 6 , x = 2(6) , x = 12 (answer) User: Solve (x + 3)2 = 36 for x. Weegy: How to Solve; 5(x-3)/4+(3/5) = (x+2)/3, for the Variable x. (An Algebra problem for Student Nurses) ... [ (x-3)+36 = 20(x+2), which is equal to 75x-225+36 = 20x+40. ] User: Solve (x + 3)^2 = 36 for x. Weegy: 72. User: (x + 3)^2 = 36 Solve for X Weegy: If (x + 3)^2 = 36, x = -9, 3. Your answers are x equals -9 and 3. (More)
Question
Expert Answered
Asked 4/16/2013 12:07:39 PM
0 Answers/Comments
What is the correct solution to 3x + 2 = -5(x – 2) ?
Weegy: 9x^4. If you are satisfied with my answer, please click 'Good' on the ratings. Thank you! (More)
Question
Not Answered
Updated 1/2/2019 6:16:39 AM
1 Answer/Comment
x + 2 = -5(x – 2) ;
x + 2 = -5x + 10 ;
x + 5x = 10 - 2 ;
6x = 8 ;
x = 8/6 ;
x = 4/3
Added 1/2/2019 6:16:39 AM
This answer has been confirmed as correct and helpful.
Solve 3x - 8.5 = 2.5x – 1.25 - .75x for x.
Weegy: 11x-10 is the answer. User: Solve for x 3x-4=2x-4/3 (More)
Question
Not Answered
Updated 4/5/2014 2:49:19 PM
2 Answers/Comments
3x - 8.5 = 2.5x – 1.25 - .75x ;

3x - 8.5 = 1.75x - 1.25;

3x - 1.75x = -1.25 + 8.5;

1.25x = 7.25;

x = 7.25/1.25;

x = 5.8
Added 4/5/2014 2:48:02 PM
This answer has been confirmed as correct and helpful.
3x-4=2x-4/3;

3x - 2x = -4/3 + 4;

x = 8/3
Added 4/5/2014 2:49:19 PM
This answer has been confirmed as correct and helpful.
32,005,374
questions answered
GET
Answers.
GET THE APP.
weegy*
*
Get answers from Weegy and a team of really smart live experts.
Popular Conversations
excretion rates of drugs vary greatly depending upon what
Weegy: Excretion rates of drugs vary greatly depending upon the type of drug involved and medical condition of the ...
8/1/2020 1:36:06 AM| 3 Answers
Resolving disputes after litigation is called
Weegy: Resolving disputes outside of court after litigation has begun is called Alternative Dispute Resolution. ...
8/7/2020 11:54:28 PM| 2 Answers
S
L
P
L
P
Points 942 [Total 6965] Ratings 1 Comments 932 Invitations 0 Online
S
L
Points 924 [Total 3921] Ratings 2 Comments 904 Invitations 0 Offline
S
L
P
R
P
R
L
P
P
C
R
P
R
L
P
R
Points 796 [Total 12887] Ratings 1 Comments 536 Invitations 25 Offline
S
L
P
1
Points 679 [Total 3535] Ratings 3 Comments 649 Invitations 0 Offline
S
L
Points 412 [Total 1905] Ratings 1 Comments 402 Invitations 0 Offline
S
L
Points 318 [Total 4702] Ratings 1 Comments 308 Invitations 0 Offline
S
L
1
Points 182 [Total 3493] Ratings 3 Comments 152 Invitations 0 Offline
S
L
Points 149 [Total 300] Ratings 4 Comments 109 Invitations 0 Offline
S
L
Points 85 [Total 244] Ratings 0 Comments 85 Invitations 0 Offline
S
L
L
Points 81 [Total 5369] Ratings 1 Comments 71 Invitations 0 Online
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.